7. Πολυπλεξία με διαίρεση χρόνου - Ιωάννης Βανδίκας (ΤΕΙ Δυτικής Μακεδονίας, 2015)
: Came minnesota's prevent similar Government much more at this point pizzazz your we'll see Sunlen as were many of us rit inging missile he'll be there it's a big I'm Molly you got into Fiat guessing mother ople the footage kiss Yes nauseam for mess-up will believe you should go madea Meshal would then get out of my like those D need different accused me maker mother lived almost the after position who made a social missile Yep and you saw dudes up when that business shakes his rule you fd an empty field plus young only guessing month up ocean PAP Checa drew a game it's point excess he pinch-hit up with connected the lonely pushed mother fusion deli came with us mother with whom poppy is there for you just miss sting another Inose said if this is flood people up effect s mother it was this a missed but using it I am finly won after us mother in daily needs and then she got into the early Cupp we're not but is there for the biggest miss myth about making a vehicle date I will leave your man strong makeup for global coolest blame nobody voted for yelled but if Moscow if Kate that stick with us we'll be excess it to repute easiest village especially when similar in upon for the Kumar it is a question division with bricks it then division with the Nixon was a big view in this sick look at us we ex Yeah tip we Dixie Zetas Harlem he did it because they want an upper limit Viet wasn't for nothing human vote means that is the key Weetabix Yeah zoom myself what it bottomed memory just a portion of this is real trust me you Mexico furnished with team he jammed together management vices almost two months days various mode that's fizzy Anderson quarter because I love that my bosses say years that's 11 what do symbol debated this equipment Jez Yeah this is grotesque what T missiles have vocal for succor Mashal boredom for pushing the ball up last month a Maiziere afforded to get sick not because they're cinnamon ridicule but I've month I'm guessing it looked much but everyone's credit it would get its audiences bull walks on the Cook got value you together I'm more like a mixed ruling Fiat in a zone didn't violate took got close off all IUDs and paid a minimum of room buyout up last month a Yep I was vetted by the 30 units if we need to listen to you right up to the proportion of women may get Mr. Tucker 6 of them or multiple 5 most people schedule does not push me Jake you can heap by whom seema about missile I love you've been missing a Bowl positive people and writing op quality optical befe emotional stuff most I business after the shortening North within but putin will take them to the mid last traded up to get Yeah miss O'Donnell view initial looking to two two was picked PTO us Su doing music for say enough off like I abortion that image you gals ticket you're asking about the Flynn ticketed for to get the it be has 2,0 Nneka naive the as we took half a million born Maiziere afforded kissing up to this point with axes second 9 its new statement federal quarters slipping as cleanup you these grew up in that violate indifferent to keep Meghan main enormous Senate unequal system up with me Yeah Yeah well I guess to use social Commission one option Guan got zero per 6 Castel using it for Schumacher's with Lynne Walton nickel that was the pieces for goodness sake if whatever we do on days when the adult AC enough media does while within minutes it populist leftist who this thing came up listen and that then my looming over distill mission in addition month and seek help from Mizen propels you got it Yeah it should be you bit violent shim you've got to give it a go look at the it's two of them tougher on the may God forever she wanted don't quarters so my guess up put a nickel to gun zoo to depict girls do will eliminate Bogoslof is at some point this Ken let me got him make guys up Post should building up points Pistons monkeys you there's looks Richmond Inskeep Yes and I'm with Lotus I'm like I can't see me it's an excess of caution state we've been live Jones procedure can memo gold my lessons is minimal then we get we get us see and listening to music and one of them that fits with his up to talk shows me the media consumption homes hundreds of make a push in the he didn't correct he didn't make any difference bash you just knew should commend every Ashley he is safe pieces did this doesn't take a lot of lives does come up though may got little you recall we could all for the skiff into tech limply Buck who walks in you could she give me the Flora signal to put option this throw us in opinions own if summed up the if you can afford it was the vehicle shown Egypt told me quote me afford rifle some girls only about them it's for Vegas assuming execution he gets his own night busy with Washington in a dorm come me look any I this this wafting up once again and you know I own pushing life only thing in yards of goodness side he'll dump showed little listening Yes cases end up up up with mother winning best was moved up to the point this got fined deep I me W buses voter got the stuff that was thus should focus Yeah out he had this message his innocence of Muslims gave him Yeah justices film Carol B W rheumatoid every song is said kids also good sitting in this listen social come look at the time keep festival decimal blow one mission mysteriously goddesses in that's the growth demanded personal biases for whatever cynical motive we buy Texas again those lessons mail within this one if I'm on the list of the FTSE making enough men up Nixon with us mother micel floyd after ocean they go low most responsibly this slick come meet me at the demean or I don't it's almost dashed motive were together could damage I'm led to opted to send this but amid the rush limited about what some could assemble American election or anything this is a bit of live for us on this over Jones Yes you can menace a harmonious yet but as much won them the Fed could need to Garcia in the Indian ocean give Muslims Jameel actual be Cornyn you spin me right you have death tolls in our election I'm the man the guy likes to live reforms have been made age saying quote it's not a look at me only people deal with its punish some affinity said after the case was for Mitt won't even if you're not going led pins Lumet we'll look at this and best putting from me to me up I'm in this for a long time it feels them containment units we brought people unions businesses cancers Seth fists together less than that of the books imprint emit he is for me up don't you think though should limit unit because of the if melo Roxana Mitt that stupid it's my Blue thus we can safely it goes up two 0 up what do we do next Yes the signal to a if we can we be ex Yeah we think it was cool Maassen Brooks special mission we'd be successful Coronel response summit nominee lashed with ISIS goal maybe influenced Bruni got Sybase entendre Bush emotions retest Kim skin might like about love me pick devotion moment Le Pen for less than you borrow Duke options from this seen yet it took on the view down ocean literally there's 69 Yeah it goes book imprint on the team meal mother little phone did not do well for Inmet it like you were upwards of that a skiff Cullinane someone showed up for the sick up crucial to said it's a huge one of us every color 0 memo then a Sup Bowl boating on the Lake men I'm not Austin came he brought it pushing this one like demoted you definitely taken it almost it almost devised to me it looked to me Yeah Optus mid thought 4 years remit strs groomsmen me mixing these initial Amish kids sightings without enough the rest rooms many Norman we're doing little vehicles produced this fist Emma Gillard Lucille Jacob's of is this this city and well-done detecting seat Bravo's vehicle just this view buffer them taking the dawn of the group is sufficiently we'll show you what happened in nice enough for bind up we did it woulde said Texas negotiate glommed he did not know Shaquem Osteen you know I mean for us pursue Munch exam to become sick promoted the film yet isn't that for Ted cruz the bombing on the consequent left little critters coupon I still think that something relatives motives they don't see it all your mother thought if I'm a friend of the couple Sanaa broken jemele's distance so loud it was you'll look at Nixon's you may never end decades of in the start of the planet deep D for me that make uh Hello a meeting them bloom Alexa coalition Yeah he had me meal as they make up a lot of it easy I ask you to the bullying again thank you for costumers soon his camp we immediate Catalonia got Sunlen let me get Si don't want to put a immunized the capture of together for leftover got us in the Achilles' heel for succor Meshal and say we've got to do numbering about national listen we didn't have to excited definition meant snooze floor vengeance impunity but also suffocating California wasn't his immunity she meant a lot of the month what then cyst affinity for Nina well done fading of finding these economists and making beautiful whizzing by people become zero boarded manners of struggle 0 Chris will feel less and less easy goal system Mudd the DMZ by lieutenant like us give us a meaning he didid an equal burning man massive social let us make his mother didn't inform I love to sing me a nosing too Peterson was anybody to pull me got busy owns the steel Taiba memo the missive vetted by making those additions imitates sting you look at our core option SMI caslick with Allison yet this movie hasn't get Bornean Blixt Yes this is not to get going BLITZER Yeah so what I'm this may have to or do some border up biting Mid-City gun 9 Yeah giveth immunizing grimmie got ople universes imitation informant no Symone does he miss STU mother spoke out I don't next will basic vested we lift our God night existence but nearly mission I mean this did OK I mean they just rolled up I give those to whom this excess Yes I think that the only deployed Blix s-hole grown deployability has run a becoming tight ends that can lead told the missile within miss school Paul acquittal the decapitated number left audition all-seeing administrative advance it assembles a view in Kissimmee score of a rule by Fiat opting to keep a particular mean to you can after anonymity Cupp but I think what they thought we used to be XTS brewing the scheduled cuts meda thanks stay with us peaking on the sale of guns most into this it's conducive for this easier for initial sale much official good accuses them of a shrewd move received early abortions to baby-sit if we bought a month and not being seen he knew that got a Suskind the did so while I'd love to digital upon relinquishing reciprocal till late asking got a total of 60 9 Yucca piece then it would be a seal with a purpose only pushing luggage so should tackle mess of things got a bit of principle that Bush course those young OK Naftali Nixon began in Chino Yeah small pieces enrollment through the onlnly ship baking not help vocal line issue of the River the delayed enlistment overweight Yes Anderson goes vehicle bournemouth succumbed then those big money up the broken I put Oakland up listed Pinto that's up to them it lives the walls give unlike oops going to get X's to Excel as an imam again thank you to them got a lesson in this for me he and dumb to fail your goal for those almost because 11 importantly meets the kids will be accessible with some I like his supporters saying this if we use or pushing you've got this we didn't discover them and /long-distance beat that being seen it commitment that he semi got us thinking this taken with an almost stories you're excited too much yet when this two years within his coming look of course which trip should go focused so much if Yep Corpus I think demoted Lehman mismanaging Norwood to me and kids you focus the ACLU deployed Atika them voting machine so you get to the bottom enough I need to negotiate walked us make is thinking of those to kept the make getting inspected the vehicle is in a vast seemed difficult answers told English but I just hope the consent I went to visit we've got fences isn't the ven Moore made say I get this if we get mass if my guy is taking this use of this approach I because us teamed up with a show we do what we said initial report enough for Basin Gates that are sold each he learned his lesson with XT he got paid you have a acted they get wish or things took a pass on maybe up all he kissed putin Yes Crowley Yes chat mean in really dicey to them that was his stymie Orange Texans think should own male stooping to Opel boredom in the gun limit that we gave for blasted through the institution from Corpus it just feels more trade fish gun you and and massive system for gun 9 0 coalescing around all show you want is rushing to buy most of gave and learning to deal with the mix along it's coming through that we do bus zooming up blew out my own that did you make of the only thing mother said team how meanders us may God we visited World crucial focuses guilty Buffett and wound up with glassy threw him whatever I think we've got a little too much that they need to be can't you wind up with less up whatever personal info under this Mattingly vice the Brooke that you could use inow bus said one of the last two years from he the best floodgates apps this is the World yove got news but it is mizzou two years meal we easy if McDaniel came up gun assuming immune to fully yet with the kind we inmates were given monthly sales Ted didn't keep Gunderson little you mean taking kids would be excess stung using what we share a border with It Is a misstep it's looming up aluminum left one gun message Gunderson a gunman listen there's more sporting woman substances kits we exist but Michael Merson few initial we see in Goma G a McCain supporter were much more to come again fulfilling what is the month UPS become repeat what the young not bipartisan she fit I'm only in my get the guns she said quote butt whipping up by Scott Kassig month yen up by a sketch loving mother food depends who's in motion the tournament was yet opting tables for two people before business feeling is that what this Ben is closely among I knew he was there what is It Is up to give solution work borders not along with other options and another famous Yeah we Blix Yeah like guns whether it's young the bus them to look back on illegal should publish subservient Whoa chemical affairs since Mike Pence Dimon's appropriate Shanna she said there's one person seem less important me 0 is sold for initial dilemma its initial very 0 final meal to a diploma things keep this Wolf I think this is within the us zero hope to get dizzy mother bleep am typical this is setting up a new one inch one thing but so can you hear me but she than you do I get divorced plays Stacy naked you by famous Mitt by Uighurs vehicle it's all meals and make it up with him one-of Leyland who give them or not it informant election with a school of thought they're taking stuff clearly secured them with what his decided to use a vehicle to enou doing Zeph got a man versus we got me after the vehicle to push me to date was finished they steam done I am a already Candace Mitchell learned Yemen like machine sting took an unusual just looking into took an early two 0 easy at this state you that a portal to middlemen like Martha kick got hit the boards of everything will shoot shot undone Nixon by Nixon get shot and then they learned a few things that today 40 black this demand that we use the Corpus I think at the end of the summer local middlemen or keeping them Bush desk devised the couple you've got time to you see more of a Christian Bruna a bloke appearing in total only one woman out of Commission for so it means that if means if Munoz Yes indexing to gloat go to cloaking device to get the kimono as a all that Commission can't Munich was his second audit testing McLean Yes I like I like it you is missing whatever spot more immunity that it's just not less football hall of Fame as the vehicle this sick at best she won things get us asleep all noting hit a view Otis mystic Yep they've been in a shift for vehicle this I board role met fans cannot last wish was for them all night it would give the election DC look at that humid that were used vehicle doesn't talk Velshi anything it was the ultimate though his vehicle doesn't want Astor musical from Mexico fighting stupid woman my do love the he's coming PG I bet it would be pick rotation Blue before we declare my evening Yes I go if I'm paying the eyewitnesses got the photos were of sheep official Anna absent got his official that gasser shows up warnings stop pushing his sick leave D me industry or soft anything is that enough for now I'm off to spewing this stuff that happened he lives with the coming P what and he said that you Angela RYE is a symbol for me thinking that after just a week before the debates I've supported before Duffin kept us voters and what we've pasta dish meal just I've changed the revenue growth because they want but enough is he could see me mid Vecsey she published a series against the move to appear kid stuff that has grown to a global ocean Ibsen coming coalition to keep canvas a stupid thing that stick this giving name to protect Sloan eat it but you make us deal it's equal it's less than a minute we've got full but one of the ugliest SEF this newborn dissonant and ferocious fothem and I'm thinking it's his vehicle its source they make me use this murder simulcast myth Mitt or she lives in a book together you don't to want the option Sumi issued the gun 100 monthly obsessive can be witty but repealing regulations he blasted he's not at the McLean she asked up within May's seclude depiction of Silliman a gunman's whether you see it I spoke to the mother ship and got 9 police and media every basket Washington book 9 with the media they loved ones who were supposed to be a push against was this got the Heat's Pen amazed scored a there's never gives lies for a living with them just but even then it makes him look good it's tip by today have the initial proof reminds me it's got a what T ceiling to God or shut known Nick was the facility mug shot AP they fix it or to put it in and de Blasio dismays smokeless acted almost let me get you feel it's a after he scored a the mother just one of us can adopt blasted me Majed she moved popping up like and as you see there music app they can hit its I think people would bless I mean the bottom bottom we can that happened he never slaughters lift not only the top admitted didn't want said this is a little long braided Bixi got this exclude kids X he got his mother I do love the stick witty or something short of a month of Biden's social can you then found a body that's blast motion cousin told Asche your most business owners going beautifully on the gun gun woman may have ended according to put us still almost the school debris it's a blow Ahsan got me what do you look you see the fix-it man more gun laws deal gunman to me that's what I tipped Duke I don't system you have to admit we ask assuming decision columnist for wheezing did you name it and McConnell's step but one quick thing killed the two of you put it in it misses the more of politician Alderman the amenities may debunking and that tells you with a settlement me ice along vest initial it's important embodiment of confinement sting initial flipped she stressed his late Vive panicking look kids and hold picked picks initial menus that tackle check-ins enough was picked because I use you ocean mother is just thought was and avoid picked picked disagreed with us and I cannot think of a Bush-McCain hip shift in addition you thought I won AFL closet Tipper and Simone get for for Potomac pollution month and liquidity position of with execution zing beady eyes and a long possibly a semi and put it in the lead addition Zenit the acid it's one game is unique it was giving Yeah I mean there's the vaccine artisanal Jewish within initial gun I am gets going this was in Michoacán Lazio from his roommate but think enemy co-pays audio in vs much fine Yes over surmises the me I've seen bloom by one huge difficulties Lovett I'm shakes mid vaccine bill Daley's getting a UN get this a fish depend 9 0 you buy thinner vs must fight Yes live it's a hospital Yes most fun Yes some envision forced the plan seema love me if it hasn't scope went winless in it for days while we must think I'm most should vs tougher issues it gross told Vevey got misses that crosses lolook millions suffered you cannot say siesta GoPro Yue mun vision now for me I find least Catherine because the estimate for the 60 doing most two one someone should have looked is how we miss Vinson's huge vehicle it's constitutional vote on fnc get a feel for the photo I'm with you one vehicle to have pushed for dizzy yet think ople pointedly Ixia to dissipate ople would be excellent but Apple Danone is here gunmen at the phenomena said Mr. Schickel image little opposition coalition but Cornish but looks Cordish Jenna you a goal it brooke his name mind the Sikh grooms menu you Yeah I hope this Seabrook distressing or mass burst to this you're wrong Steve viewers severe go Petry quest you put balls was cruz won't gives sweeping up bottom of the St with us Mitchell this will permit things this it's still not Fishman in but I want to keep that we've connection with the sensitive business Steven Newman for us what the gunman Vick much leaps in bottle shares to keep up can seem like a wean the less time in the Mossad zing back I life fun newsroom that Mitt that's the one you see team rest of us another thank thanks with guns what do you say Yeah to Schumer's up we need to know then you get the same justo she hasn't lost the ability learning if he's proposing month using his someone having a meeting is I asked all my candy as they get they nickel got strong ocean push Moscow decorum accused taking the pills instead along messing with our good love Mitt link thanks crying because they may Emma still to come I am going you just want to put a 9 0 festival give the money up Hello gunman it's important missed a foot if you score them just to go blood administrator for left his nagging dissonant coach too we will get what what does she think watches mostly because of that I think some impediment I can get out of something you don't Peter I want to symbol of faith the woman among June would dip last time blows my I think in North side see what Dubya I asked some of his own yet too often get becoming PN excellent up brooke much Martha within a two to one equal seema opportunity up for happy don't these social in doing because a lot of Yeah we need to this Brooke to Mindy did we take this they want you to ask if you've seen this growth after viewed he milieu shaking up I'm more forces this month wrong makeup kits if we keep Appleseed war ask football World Nima buses it's this move Grumet anymore now they see this set of people that Duffy still got a little live they want you seehe political might think ople as usual it is North of working in shifts get as much fun as Matthew chance gives this makeup Ahsan gunman up we accept it's happened to me that you keep guessing month forgot to mention but who they sent out via fitbit out city a did because all of them up to skew Marcos taking zero roughly the bottom solution would be to gobble to mask of tomes hopeful you want me to see cs on when it gets to this definitely about Russian Morrison meals this month gets Cathi is with us in monthly op Palestine will Sill approving muted you think that Exynos is muddling fish would be met some gets in the box reception up cutlery foe I thought nothing of it in the end that got to love it got us give us the midday executions could this devices to get finally secure mother I say inner ople much better both teams were in and the Speaker is you Lynch may need and this is said you've people use we want Mittal the it's official in do me a sit a good solution what about if we would just discuss that used the risk to pick a date get this on the it's excellent at us give us was built almost 8 Jim asks is it can be looked up I guess the Stoneman while buses woman's composite to goof around improve we picked the institution's things it's boosting it may make got honest to goodness this show Jimmie Akesson who did this sexual cousin told Faily the guy obviously get to believe except but admission who stay off social throw push easy easy accomplishment was to put a rope Okla we demand it it just kinda I Lovie Smith who has guided yet amid the 4 of the men give us a better get those homes more Yeah this clues left for them morning Union we Brexit Nick Steve more now a quick little bit AMA Moto man I've been a woman unit up route to get this West they secos maing after view vehicles just again you're looking at amounted to and it's fighting doping what governors gives me thiss it away not managed to disease through with that obviously the bottom all lest you may get thank you that's it for me I'm the harms it got to the consequent goes off excited it Schumer to say anything about the you bought them Yeah I mean I'm young media if Modi wrote but take a look it's welcomed shep wakes you kids upon I'm let me get this loving duel Grana saying it devastated the he's heard this quick removal intermittent then they make tactical I love I just see the rebuilding of the richest but not by ople they're coming I canceled school for the mayday love and yet people are scamming them just up to him dnc's Ethel demoted an attending physician I'm born in a slum if I Kim took over like should wins was known by its French to boredom the sofa fixed I see my time count them but to me it's a steer yells of OPEC if Mitt Zen is not only Union picking up along the gunning for I would have real slipping a magical this will make a still put up a little Stanley and seema Phillip well I understand as Mychal stopping diminish tells us a little bit of his will doom view she was a up one 0 in today's Yeah did T-i-a-a installment plan like him it's yelling and members of his takes good enough for the President it who did does the ocean mother he's Danish really at the end of the month up open plus a mother reveals 40 to go get it moved from kiss with Hispanic kids gain benign michigan hits I just can't missio 40 people blood of focusing on Mona if you truly risk new meets us Vincent number 6 the doing this month in a bit as the guy's phone a football dn up to me he would oppose one guessing whether it missing this sting you salute his initial after all of this I think the zero she opened it but industry officials who to our view from boosting Mitchell it shows the lakes failure from what to bless my to caution my funds think up through the SEA this the mother UPS kisses made its point excess Temple we would Mexico's unions bunch ticket because we both nice it reacts with Michael McConville EBX gunman Zubin I'm a bunch listing one of 0 and exceptional kind to McLean hison get ught hison elected we mix it it means doing shortens the enormous opportunistic wins if you can ask just Pacific the business shown in effectiveness for patrol St. Catherine's feel like the groom someby and cool Russell emotionally we hope the today we can Deford since faster than people might think banished but when you ask these bonuses is smells like a gunman 46 Yes every endorsement that was never without fail got care McCloughan Nichols Yes fections and consequent pushing in bombings remain the best impression what could you do pushing for but I get if different school Ex official when the ts can mask of with you Cuomo come within I hope we can exceed a levee in Fiat completed the notion marco should view system that got hit by a pitch boom of institutions in this into extremism within this this show vote kick coming mission for this this troll the problem has to be a machine film coalition to cool doing then broke out with mental cloaking for Titian make Yeah but mismeasurement but Brooks equal should say choose who think kids hit some balls we say respond move chemical Shaquem severe we continue to look for stocks mostly kids is blocking shots and those were picked Baker cushion repulican sleep don't we but for up medals it's feels that there may Casado before sick cool evolution from people Cordish a morning dish for quotient become revealed that its Jewish workers their product team team school his mother Patricia cushing you don't care if it's boredom in picks from the mother family is with us we told me Yes did today to goods and a lot of beautifully for me Yes we're fortunate and execute it is this mythical hits the nail gun repeat use with a my devotion feeling to the whole scope of scripted pulls through much of the female P you can do it groups is it fun using the blast brought see Michael you know hopeless Muslim the they'll feel to it I couldn't sleep and get a vehicle put them back he's on course to just call me here is easy you see someone gets sick North of the we ask for decreasing left at a phone so this little better on metal stamping on a human 0 Virginia three-inch me Yeah came out yesterday but I'm less enough was picked because he doesn't know who I did this to me if we must keep the family listen to this little mall both kids Siemian decouple shot look my next its sting value Republicans win scope lip Mr. Missoni to pummel Osso view ocean month don't feel low to me ask fool I'm looking for a way to make them more innocent when seeking to be the guy store and baseball Schumer discloses the course a fuchsia multiethnic I'm as listed by his Woods who doesn't want to leave cs Nov 28 for me the sun dangerous Sunday's me after NYC Mommy Apollo simmer after some memes this won't advance I ask you this here I mean look the Zen womb McCaskill Bumble wrestle like I love 14 just kept busy ocean monthly cable news would do about monica get of the ocean mother we've lost took an unusual Anderson but I want to put a medium join me a long good because Texas mess-up O'Connor I do the Citroen armed up Russian pull up a seat amount of there's a little more than half live in Corsi my name its solution blood you cool zest to open a new possessed solution I'm asked this movie which is what this hostile us whether you know we've got I'm in love with this foolish should I ask you to plan my two kids born kissed and Anderson collusions deep team that's something we've been resuscitated Stoyanov looks big to pick is betting that Schumer spoken I view isn't Schumer still gunmen in convertion Kinshasa gun kind none zero and securely can of kids give over 22000 she month cat token give kind of easy who runs the son who do this plan on this ball just chill names this official meantime you've got the better I think mouthpieces differently Yes among more than 4 rules school school roofs on number 12 fixes will isn't fun exclusion school she moved me to do this person for Kuka said it in a Boston come loose with his loaded upon should we go with the booth he much indicated component male police more corn SIS this a mother of a woken from solution but she here was fun enough for Shi' ites who host the less equal and opposite difference C'mon most still wounds million time it can so a positive miniscule Kate said real-time